Multimodal Magnetic Resonance and Photoacoustic Imaging of Tumor-Specific Enzyme-Responsive Hybrid Nanoparticles for Oxygen Modulation - Sivasubramanian, Maharajan; Chu, Chia-Hui; Cheng, Shih-Hsun; Chen, Nai-Tzu; Chen, Chin-Tu; Chuang, Yao Chen; Yu, Hsia; Chen, Yu-Lin; Liao, Lun-De; Lo, Leu-Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Multimodal imaging contrast agents for cancer that can not only perform diagnostic functions but also serve as tumor microenvironment responsive biomaterials is encouraging. In this study, we report the design and fabrication of a novel enzyme responsive T1 magnetic resonance imaging (MRI) contrast agent that can modulate oxygen in the tumor microenvironment by the catalytic conversion of H2O2 to O2. The T1 contrast agent is a core-shell nanoparticle that consists of manganese oxide and hyaluronic acid (HA) conjugated mesoporous silica nanoparticle (HA-MnO@MSN). The salient features of NP developed in this study are: 1) HA serves as a targeting ligand for CD44-expressing cancer cells; 2) HA allows controlled access of water molecules to the MnO core by the digestion of enzyme hyaluronidase; 3) the generation of O2 bubbles in the tumor by consuming H2O2 and 4) capability to increase the oxygen tension in the tumor. The r1 relaxivity of HA-MnO@MSN was measured to be 1.29 mM−1s−1 at a magnetic field strength of 9.4 T. In vitro results demonstrated the ability of continuous oxygen evolution by HA-MnO@MSN. After intratumoral administration of HA-MnO@MSN to a HCT-116 xenograft mouse model, T1 weighted MRI contrast was observed after 5 h post-injection and retained up to 48 h. In addition, in vivo PA imaging of HA-MnO@MSN demonstrated an increase in the tumor oxygen saturation overtime after i.t. administration. Thus, core-shell nanoparticles developed in this study could be helpful in tumor-targeted T1 MR imaging and oxygen modulation.